Deposition of substituted apatite coatings at different coating patterns via drop-on-demand micro-dispensing technique. (12th May 2018) - Qiu, Xihe; Lim, Poon Nian; Tong, Shi Yun; Thian, Eng San
Abstract: Silicon-substituted hydroxyapatite (SiHA) and silver-substituted hydroxyapatite (AgHA) potentiated their usages as bone graft materials with favourable bioactivity and enhanced antibacterial properties, respectively. To facilitate bone growth and reduce bacterial adhesion simultaneously, multi-material coatings composed of SiHA and AgHA at ratios of 1:1, 1:2, 1:3 (1SiHA-1AgHA, 1SiHA-2AgHA, 1SiHA-3AgHA), were deposited by different coating patterns via a Drop-on-Demand (DoD) micro-dispensing technique. As an additive manufacturing technique, placement, size, and numbers of droplets could be controlled precisely, and this gave rise to an even distribution of SiHA and AgHA, which integrated functional properties to a thin coating layer of 9·0 ± 0·5 μm. From the antibacterial study, SiHA-AgHA coatings, especially 1SiHA-3AgHA coatings demonstrated an inhibition on the growth of Escherichia coli ( E. coli ) up to 12 h as compared to pure HA and SiHA coatings.